A Wet-Stock Management and Leak Detection System for Fuel Tanks - Ayşe Nur Dalman; Murat Oluş Özbek (Journal of Advanced Research in Natural and Applied Sciences)
One of the critical problems in wet-stock management is inaccurate (poor) tank calibration that masks the leakages from the underground storage tanks (USTs). Moreover, obtaining the correct tank parameters or re-calibration is an expensive procedure if not impossible. This study aims to prevent the masking effect of several tank parameters on the tank calibration chart and to improve the leak detection and wet-stock management for fuel storage tanks. This goal is achieved through obtaining the mathematical models for simple cylindrical tank that convert the measured liquid height to accurate liquid volume by taking into account the tank deformations. The accounted defor-mations in tank parameters are errors in radius, length, probe offset and axial and radial tank tilts, as well as volume change with temperature. The simulations using the actual data gathered from a commercial fuel service station showed that the approach developed in this study is valid. The deformation included tank models successfully pre-dicted the real fuel volumes. The results showed that the variance reduced from -300 L – +100 L range to -20 L – +20 L range for, which brings 67.2% improvement over the cumulative variance. This study also shows that obtaining the precise volume measurements by introducing models that account for the deformations in the UST is possible.